Charged carbon nanomaterials: the redox chemistries of fullerenes, carbon nanotubes, and graphenes - Shaffer,MSP; Clancy,A; Skipper,N; Howard,C; Bayazit,MK; Hodge,S (Chemical Reviews, 2018)
Since the discovery of buckminsterfullerene over 30 years ago, sp2-hybridised carbon nanomaterials (including fullerenes, carbon nanotubes, and graphene) have stimulated new science and technology across a huge range of fields. Despite the impressive intrinsic properties, challenges in processing and chemical modification continue to hinder applications. Charged carbon nanomaterials (CCNs), formed via the reduction or oxidation of these carbon nanomaterials, facilitate dissolution, purification, separation, chemical modification, and assembly. This approach provides a compelling alternative to traditional damaging and restrictive liquid phase exfoliation routes. The broad chemistry of CCNs not only provides a versatile and potent means to modify the properties of the parent nanomaterial but also raises interesting scientific issues. This review focuses on the fundamental structural forms: buckminsterfullerene, single-walled carbon nanotubes, and single-layer graphene, describing the generation of their respective charged nanocarbon species, their interactions with solvents, chemical reactivity, specific (opto)electronic properties, and emerging applications.